Practical interventions for young people at risk - Geldard, Kathryn; Sage eBooks (Los Angeles, [Calif.] ; London : SAGE, 2009)
Focusing on interventions that practitioners can use in collaboration with the young person, this book offers hands-on strategies for enhancing resilience and addressing challenges and issues typically faced by young people. Topics covered include: depression, suicide, and self-harm; substance abuse; problematic sexual behaviour; marginalised youth; mental health issues; peer mentoring and building on strengths; cults and gangs; bullying; firelighting. Throughout the book, multi-disciplinary and international authors share their expertise, highlighting relevant evidence-based interventions and considering themes such as anti-oppressive practice, culture, values and ethics.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Social work with youth; Social work with teenagers; Problem youth -- Services for; Problem youth -- Counseling of; Electronic books